The Grouchy Ladybug - Carle, Eric (New York HarperCollins, 1996)
A grouchy ladybug, looking for a fight, challenges everyone she meets regardless of their size or strength.
Keywords: Ladybugs -- Fiction; Human behavior -- Fiction